Comparação da qualidade microbiológica de queijos tipo parmesão ralados industrialmente e no comércio varejista no Estado de São Paulo, Brasil - Aguilar, Carlos Eduardo Gamero [UNESP]; Rossi Junior, Oswaldo Durival [UNESP]; Vidal, Ana Maria Centola; Ribeiro, Laryssa Freitas [UNESP]; Rossi, Gabriel Augusto Marques [UNESP] (FapUNIFESP (SciELO), 2016)
With the objective to evaluate the hygienic and sanitary conditions of grated parmesan cheese acquired from the retail business, total 120 cheese samples were acquired: 60 of which were obtained from four different brands of cheese that were grated in factories, and the other 60 samples were obtained from another four brands of cheese that are normally acquired by retailers (supermarkets) in blocks and grated at the moment of sale. The population of heterotrophic mesophilic microorganisms ranged from 1.2×103 to 1.1×107 colony-forming units (CFU)·g-1. All samples analyzed contained Staphylococcus spp. with populations varying from 1.2×103 to 8.7×106CFU·g-1, from which 60.0% were classified as coagulase-positive Staphylococcus and 52.5% of the samples possessed populations above the permissible limit set by legislation. Staphylococcus aureus was detected in 57.5% of the samples. Population of molds and yeasts varied from <10 to 1.8×106CFU·g-1. Salmonella spp. was not isolated in this research. A difference was observed between the parmesan cheese grated in factories and that grated in supermarkets, where the former presented better microbiological quality than the latter. Thus, procedures must be proposed to minimize the presence of pathogenic agents reported in grated parmesan cheeses evaluated in the present study because of the public health risk associated with food bacterial contamination.
Microbial quality of industrial and retail market grated parmesan cheese in the State of São Paulo, Brazil
Keywords: Dairy; Food microbiology; Public health; Staphylococcus aureus